REACTIONS TO DAVID TRUBEK AND CAMILA ALVES - Prado, Mariana Mota; Trebilcock, Michael J. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
David Trubek and Camila Alves focus their reactions on the concept of spontaneous institutional bypasses, offering a potential case study. We are deeply grateful to them for engaging with the concept we offered and also setting a potential agenda for future research. We are hoping that our book will stimulate not only normative studies that set the parameters to distinguish successful and unsuccessful bypasses (see our response to Machado, in this volume), but will also incentivize the kind of descriptive analysis developed by Trubek and Alves. The descriptive analysis basically consists of exploring other examples that may also be characterized as what we call an institutional bypass. Offering a concrete example for researchers to explore, as Trubek and Alves do, is certainly of great value.